The role of connexin 37 gene polymorphism (1019C > T; Pro319Ser) in cardiovascular disease - Pitha, J.; Pithova, P.; Hubacek, J.A. (Вiopolymers and Cell, 2011)
In spite of the strong prognostic value of all traditional cardiovascularrisk factors, still striking differences exist
in the prevalence of clinical events between patients at apparently similar risk. One of the main reasons is
different genetic background. One of recently discussed candidate genes for cardiovascular disease is the gene
for the protein Connexin 37 (Cx37). This protein is a part of gap junctions responsible for communications between cells including cells in the vessel wall. Studies focused on the association between Cx37 gene polymorphism (1019C > T; Pro319Ser) and cardiovascular disease demonstrate inconsistent results. Our findings in
1.316 men and women indicated that the Cx37 gene polymorphism (genotype CC) is significantly associated
with acute coronary syndrome in non-smoking women. In addition, in urban and rural women from general population (n = 1.056) with impaired fasting glycaemia the same genotype is associated with increased intima
media thickness of carotid arteries measured by ultrasound. Finally, in 289 women with diabetestype 1 or 2, and
in 208 women from general population with central obesity, the CC genotype was associated with lower ankle
brachial blood pressure index. These data indicate that Cx37 gene polymorphism could have gender- and smoking-dependent effects on acute coronary events and glucose dependent effect on atherosclerosis in women.
Keywords: connexin 37 gene polymorphism, atherosclerosis, acute coronary syndromes, women smoking,
glycaemia. Незважаючи на однозначність прогностичного значення усіх
традиційних факторів ризику серцево-судинних захворювань,
існують значні розбіжності у їхніх клінічних проявах у різних
пацієнтів. Однією з основних причин цього є неоднаковий генетичний фон. З-поміж недавно обговорюваних генів-кандидатів, які впливають на серцево-судинні захворювання, обрано
ген білка конексину 37 (Cx37). Цей білок відповідає за міжклітинні взаємодії, включаючи клітини стінок кровоносних судин. Дослідження, зосереджені на пошуку зв’язку між поліморфізмом гена конексину 37 (1019C > T; Pro319Ser) та серце -
во-судинними захворюваннями, показують суперечливі результати. Наші дослідження 1316 чоловіків і жінок демонструють, що поліморфізм гена Сх37 (генотип СС) значною мірою
пов’язаний з гострим коронарним синдромом у жінок, які не курять. Окрім того, у міських і сільських жінок із загальної популяції (n = 1056) з порушеною глікемією цей же генотип пов’язаний із збільшенням товщини інтими сонних артерій, виміряної ультразвуком. У 289 жінок з діабетом 1-го або 2-го
типу і у 208 жінок із загальної популяції з ожирінням генотип
СС виявився зв’язаним з нижчим щиколотко-плечовим індексом тиску крові. Такі дані показують, що стать і куріння діють на гострі коронарні прояви, обумовлені поліморфізмом гена Cx37, для жінок виявлено також глюкозозалежний вплив на
атеросклероз.
Ключові слова: поліморфізм гена конексину 37, атеросклероз, гострий коронарний синдром, куріння жінок, глікемія. Несмотря на однозначность прогностического значения всех
традиционных факторов риска сердечно-сосудистых заболеваний, по-прежнему существуют значительные отличия в их
клинических проявлениях у разных пациентов. Одной из основных причин этого является неодинаковый генетический фон.
Среди недавно обсуждаемых генов-кандидатов, влияющих на
сердечно-сосудистые заболевания, выбран ген белка
коннексина 37 (Cx37). Этот белок ответствен за межклеточные взаимодействия, включая клетки стенок кровеносных сосудов. Исследования, сосредоточенные на поисках связи
между Cx37 полиморфизмом гена (1019C > T; Pro319Ser) и сердечно-сосудистыми заболеваниями, показывают противоречивые результаты. Наши исследования 1316 мужчин и
женщин демонстрируют, что полиморфизм гена Cx37 (генотип СС) в значительной степени связан с острым коронарным
синдромом у некурящих женщин. Кроме того, у городских и
сельских женщин из общей популяции (n = 1056) с нарушенной
гликемией тот же генотип связан с увеличением толщины интимы сонных артерий, измеренной ультразвуком. У 289 женщин с диабетом 1-го или 2-го типа и у 208 женщин из общей
популяции с ожирением генотип СС оказался связанным с более низким лодыжечно-плечевым индексом давления крови.
Эти данные показывают, что пол и курение действуют на
острые коронарные проявления, обусловленные полиморфизмом гена Cx37, для женщин выявлен также глюкозозависимое
влияние на атеросклероз.
Ключевые слова: полиморфизма гена коннексина 37, атеросклероз, острый коронарный синдром, курение женщин, гликемия.